2020
DOI: 10.1016/j.nmni.2020.100729
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping and drug susceptibility testing of Mycobacterium tuberculosis in Iran: a multi-centre study

Abstract: Tuberculosis (TB) is a deadly infection and caused 1.4 million deaths in 2018. Assessing the geographic distribution of major lineages of Mycobacterium tuberculosis can contribute greatly to TB control. Mycobacterial interspersed repetitive unit variable number tandem repeat (MIRU-VNTR) typing is commonly used to differentiate various lineages of M. tuberculosis . A total of 2747 clinical specimens were collected consecutively from October 2018 through June 2019. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The leading cause of infertility is not clear, but it is assumed due to different risk factors, including smoking, alcohol consumption, changes in sexual behaviour, and even infectious diseases, meaningful increase in the prevalence rate of infertility can be observed. Among different infectious risk factors, the role of various viruses has attracted much attention (Abedi et al., 2018; Arefzadeh et al., 2020; Boeri et al., 2019; Garolla et al., 2013; Ghasemnejad et al., 2018; Khajehzadeh et al., 2018; Mahmoudi et al., 2019; Mousavi et al., 2020; Nasiri et al., 2020; Pormohammad et al., 2019; Pourentezari et al., 2016; Schuppe et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The leading cause of infertility is not clear, but it is assumed due to different risk factors, including smoking, alcohol consumption, changes in sexual behaviour, and even infectious diseases, meaningful increase in the prevalence rate of infertility can be observed. Among different infectious risk factors, the role of various viruses has attracted much attention (Abedi et al., 2018; Arefzadeh et al., 2020; Boeri et al., 2019; Garolla et al., 2013; Ghasemnejad et al., 2018; Khajehzadeh et al., 2018; Mahmoudi et al., 2019; Mousavi et al., 2020; Nasiri et al., 2020; Pormohammad et al., 2019; Pourentezari et al., 2016; Schuppe et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The NEW-1 sub-lineage was identified as the dominant (21.9%) circulating genotype in Iran by a systematic review of studies of the last decade (Hadifar et al 2021 ). In a multicenter study covering nine Iranian provinces, the NEW-1 sub-lineage made up the most (41.2%) resistant isolates (Mousavi et al 2020 ). Recently, a hypothesis has been put forward about the origin and dispersal of this sub-lineage: its ancestor originated in China centuries ago, entered Iran through the invasion of the Mongol Empire about 800 years ago, and gradually evolved into NEW-1.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, 15-locus and even 12-locus analyzes were more discriminative than 24-locus analysis for our isolates (HGDI = 0.943 and 0.867 compared to 0.835, respectively). Numerous studies in Iran have reported the discriminatory power of 15-locus MIRU-VNTR analysis to be very high (HGDI ≥ 0.98) and desirable for the genotypic differentiation of MTB (Kochkaksaraei et al 2019 ; Azimi et al 2018 ; Mousavi et al 2020 ). Nevertheless, a study in China calculated the HGDI of 12-, 15-, and 24-locus analysis for 668 isolates at 0.925, 0.996, and 0.998, respectively (Shi et al 2018 ), which is inconsistent with the present study for the 24-locus analysis.…”
Section: Discussionmentioning
confidence: 99%
“…At least five members of Herpesviridae , including CMV, EBV, HSV‐1, HSV‐2, and VZV, which spread around the world, can cause tumorigenic transformation, and gene overexpression 8 . The most common clinical symptoms of patients, suffering from these viral health problems, are blisters, fever, meningitis, changes in an individual's behavior, cognitive disability, aphasia, seizures, and neuropsychological deficits 9,10 . Immunocompromised people, such as AIDS patients and organ‐transplant recipients, usually have these symptoms as these viruses are opportunistic pathogens 11,12 Moreover, Enterovirus ( EV) is another virus that can be considered one of the leading causes of aseptic meningitis in children 13‐15 .…”
Section: Introductionmentioning
confidence: 99%
“… 8 The most common clinical symptoms of patients, suffering from these viral health problems, are blisters, fever, meningitis, changes in an individual's behavior, cognitive disability, aphasia, seizures, and neuropsychological deficits. 9 , 10 Immunocompromised people, such as AIDS patients and organ‐transplant recipients, usually have these symptoms as these viruses are opportunistic pathogens 11 , 12 Moreover, Enterovirus ( EV) is another virus that can be considered one of the leading causes of aseptic meningitis in children. 13 , 14 , 15 This virus, accounting for 60%–80% of all aseptic meningitis cases, belongs to Picornaviridae .…”
Section: Introductionmentioning
confidence: 99%